Aesthetic athletes` reflections on early specialization: a self-determination theory perspective - Downing, C.; Redelius, K.; Nordin-Bates, S. M. (The Sport Psychologist, 2025)
Despite the suggested risks concerning lower enjoyment and dropout, early specialization is said to be beneficial for high-level performance in aesthetic sports. In this study, we investigated in what ways early-specialized aesthetic athletes reflect upon their motivation throughout their training history. Ten Swedish high-level athletes who specialized early (two figure skaters, three artistic gymnasts, and five team gymnasts), age 18-24, participated in semistructured interviews. The interviews were analyzed using reflexive thematic analysis. Results are presented as three themes whereby one foundational theme, sustained autonomous motivation, underpins the other two themes: early engagement and intensified engagement. The results indicate that the interviewed athletes maintained autonomous motivation throughout their early specialization and their continued athletic career. This autonomous motivation remained despite experiences of external and introjected motivation during adolescence. As such, our results support a multifaceted profile perspective of motivation.